2017
DOI: 10.3343/alm.2017.37.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Soluble ST2 and High-Sensitivity Troponin I in Predicting Short-Term Mortality for Patients Presenting to the Emergency Department With Chest Pain

Abstract: Background: High-sensitivity cardiac troponin I (hs-cTnI) and the soluble isoform of suppression of tumorigenicity 2 (sST2) are useful prognostic biomarkers in acute coronary syndrome (ACS). The aim of this study was to test the short term prognostic value of sST2 compared with hs-cTnI in patients with chest pain.Methods: Assays for hs-cTnI and sST2 were performed in 157 patients admitted to the Emergency Department (ED) for chest pain at arrival. In-hospital and 30-day follow-up mortalities were assessed.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 39 publications
3
32
0
Order By: Relevance
“…Elevated levels of sST2 remained an independent predictor of MACE in the regression analysis. These observations concur with previous studies where sST2 was reported to successfully predict mortality within 30 days of emergency department admission . In another study, elevated sST2 levels were associated with increased risk of both CVD and HF .…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Elevated levels of sST2 remained an independent predictor of MACE in the regression analysis. These observations concur with previous studies where sST2 was reported to successfully predict mortality within 30 days of emergency department admission . In another study, elevated sST2 levels were associated with increased risk of both CVD and HF .…”
Section: Discussionsupporting
confidence: 91%
“…These observations concur with previous studies where sST2 was reported to successfully predict mortality within 30 days of emergency department admission. 20 In another study, elevated sST2 levels were associated with increased risk of both CVD and HF. 21 A higher concentration of sST2 was also reported to predict long-term mortality in acute STEMI patients who underwent percutaneous coronary intervention.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alternative strategies also include investigating the use of hsTnT when used with other biomarkers, such as soluble isoform of suppression of tumorigenicity 2 (sST2), which has been shown to be useful in prognosticating 30-day cardiac mortality among ED patients with chest pain. (31) While the rise and fall of cardiac biomarkers is one of the components in the diagnosis of MI, (5) the link between delta-hsTnT and future MACE is less established. Among patients with NSTEMI, relative delta-hsTnT of 20% was linked to higher long-term mortality, and 30-day mortality was similar across quartiles of relative delta-hsTnT.…”
Section: Discussionmentioning
confidence: 99%
“…ST2 can be measured using a commercially available immunoassay and is cleared by the US FDA (86). In a recent study, the prognostic value of sST2 compared with hs-cTnI was examined among sequential patients presenting to the ED with chest pain (87). Interestingly, soluble ST2 levels at time of presentation showed higher independent predictive power than hs-cTnI for cardiovascular events.…”
Section: Assays For Detection Of Acute Coronary Syndromementioning
confidence: 99%